1997
DOI: 10.1038/bjc.1997.479
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D analogues up-regulate p21 and p27 during growth inhibition of pancreatic cancer cell lines

Abstract: Summary To obtain information regarding the growth-inhibitory effect of 1,25-dihydroxyvitamin D3 and its non-calcaemic analogue 22-oxa-1,25-dihydroxyvitamin D3 on pancreatic cancer cell lines, differences in the effects of Gl-phase cell cycle-regulating factors were studied in vitamin D-responsive and non-responsive cell lines. Levels of expression of cyclins (D1, E and A), cyclin-dependent kinases (2 and 4) and cyclin-dependent kinase inhibitors (p21 and p27) were analysed by Western blotting after treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 22 publications
3
76
0
7
Order By: Relevance
“…A number of genes are regulated by 1,25D 3 and its analogues, including the cyclin-dependent kinase inhibitors (CDKI) p21 WAF-1 and p27 Kip1 (Liu et al, 1996;Wang et al, 1996;Matsumoto et al, 1998). Both these proteins have been shown to be up-regulated in the pancreatic cancer cell line BxPc-3 after treatment with 1,25D 3 as well as the synthetic analogue 22-oxa-1,25-dihydroxyvitamin D 3 (OCT) (Kawa et al, 1997), implying that this is the mechanism whereby G0/G1 arrest is achieved. p21 WAF-1 can also protect cells from apoptosis in some systems (Gartel and Tyner, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes are regulated by 1,25D 3 and its analogues, including the cyclin-dependent kinase inhibitors (CDKI) p21 WAF-1 and p27 Kip1 (Liu et al, 1996;Wang et al, 1996;Matsumoto et al, 1998). Both these proteins have been shown to be up-regulated in the pancreatic cancer cell line BxPc-3 after treatment with 1,25D 3 as well as the synthetic analogue 22-oxa-1,25-dihydroxyvitamin D 3 (OCT) (Kawa et al, 1997), implying that this is the mechanism whereby G0/G1 arrest is achieved. p21 WAF-1 can also protect cells from apoptosis in some systems (Gartel and Tyner, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which these compounds generate inhibition of proliferation and induction of apoptosis in tumor cells are not fully understood. The inhibition of cell proliferation mediated by VD3 compounds has been reported to be due to modulation of cell cycle regulators and a G1 phase arrest through induction of p21 and p27 in pancreatic and breast cancer cells (Kawa et al, 1997;Wu et al, 1997;Verlinden et al, 1998). However, another report showed that VD3-induced G1 arrest is associated with a significant decrease of p21 and increase of p27 in squamous cell carcinoma cells (Hershberger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased expression of both p21Waf1 and p27Kip1 protein has been observed upon di erentiation of myeloid cells, prostate cells, glioma, oligodendrocytes and erythroid progenitors (Chen et al, 1999;Ghiani et al, 1999;Harvat et al, 1998;Muto et al, 1999;Panzenbock et al, 1998;Zi and Agarwal, 1999) and in vitamin D-induced arrest of tumor cells (Kawa et al, 1997). In normal keratinocyte (Harvat et al, 1998) and megakaryocyte (Taniguchi et al, 1999;Urashima et al, 1997) di erentiation, p21Waf1 upregulation immediately precedes increased levels of p27Kip1 protein.…”
Section: Introductionmentioning
confidence: 99%